PRINSIP ISLAM DALAM MELINDUNGI HAK MINORITAS - Novianti, Linda (ADLIYA: Jurnal Hukum dan Kemanusiaan, 2021)
This study aims to encourage the creation of a sense of security and peace for religious minorities in carrying out their obligations as religious communities. This study shows that minority rights are one of the most difficult problems faced by Muslims in today's context. In fact, minority rights have been regulated in the Al-Quran and were directly practiced by the Prophet Muhammad when leading Medina and confirmed in the form of the constitution of Medina. This study uses a qualitative normative approach. The results of this study conclude that Islam as a religion that teaches its people that plurality and plurality are sunatullah which need not be questioned as long as they do not contradict the principles of faith and human rights. Then Islam observes that the protection of minority rights is the prevention of economic, social, cultural, political and legal discrimination with the aim of equalizing positions without imposing boundaries based on differences from one another.